Dragonfly in amber ebook - Gabaldon, Diana (Outlander, 2004)
NEW YORK TIMES BESTSELLER • The second book in Diana Gabaldon’s acclaimed Outlander saga, the basis for the Starz original series. “A triumph! A powerful tale layered in history and myth. I loved every page.”—Nora Roberts   With her classic novel Outlander, Diana Gabaldon introduced two unforgettable characters—Claire Randall and Jamie Fraser—delighting readers with a story of adventure and love that spanned two centuries. Now Gabaldon returns to that extraordinary time and place in this vivid, powerful sequel to Outlander .   For twenty years, Claire Randall has kept her secrets. But now she is returning with her grown daughter to the mysteries of Scotland’s mist-shrouded Highlands. Here Claire plans to reveal a truth as shocking as the events that gave it birth: the secret of an ancient circle of standing stones, the secret of a love that transcends centuries, and the truth of a man named Jamie Fraser—a Highland warrior whose gallantry once drew the young Claire from the security of her century to the dangers of his.   Claire’s spellbinding journey continues through the intrigue-ridden French court and the menace of Jacobite plots, to the Highlands of Scotland, through war and death in a desperate fight to save both the child and the man she loves. BONUS: This edition contains an excerpt from Diana Gabaldon’s Voyager .